Adventurers’ adventures: Can they relaunch outdoor activities after Covid? - Werther Giannini (Ricerche di Pedagogia e Didattica)
In this article, I highlight how the lockdowns during the pandemic in Italy favoured the emergence of a higher indoorisation for Generation Z. I underline the fact that the most recent post-pandemic studies in Italy highlight the difficulties for a part of adolescents to resume experiential activities in outdoors. The latest research states that some teenagers do not find the stimuli to get out of the virtual bubble after the end of the pandemic. Some scholars of outdoor education in Italy have started a debate on whether it is enough to give adolescents the opportunity to resume outdoor experiential activities for a real re-start, or whether the adventurers’ adventures can be an example to follow. The scientific literature in outdoor adventure education has not yet explored the positive relationship that can be established between pupil and adventurer in order to promote more place-based micro-adventures.